2021
DOI: 10.3390/mps4020037
|View full text |Cite
|
Sign up to set email alerts
|

POIS-10 Māori: Outcomes and Experiences in the Decade Following Injury

Emma H. Wyeth,
Sarah Derrett,
Vicky Nelson
et al.

Abstract: Injury-related disability burden extends well beyond two years post-injury, especially for Māori (Indigenous) New Zealanders. Māori also experience greater difficulty accessing health services. This prospective cohort study extension uses mixed-methods and aims to understand and identify factors contributing to long-term experiences and outcomes (positive and negative) at 12 years post-injury for injured Māori and their whānau (families), and explore the barriers and facilitators to whānau flourishing, and acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 39 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…This paper presents findings from qualitative analyses of “free-text responses” collected during telephone interviews occurring as part of paired studies being undertaken as the COVID-19 pandemic unfolded in 2020. The Health Research Council of NZ funded the paired studies -the ‘Prospective Outcomes of Injury Study: 10 years on’ (POIS-10; HRC19/344) and ‘POIS-10 Māori: Outcomes and experiences in the decade following injury’ (HRC19/325) following cohorts of New Zealanders recruited between 2007 and 2009 following an injury ( Derrett et al, 2021 , Wyeth et al, 2021 ). These studies aim to understand longer-term health and well-being outcomes for cohorts of NZ adults, including specifically for Māori (NZ’s Indigenous population).…”
Section: Introductionmentioning
confidence: 99%
“…This paper presents findings from qualitative analyses of “free-text responses” collected during telephone interviews occurring as part of paired studies being undertaken as the COVID-19 pandemic unfolded in 2020. The Health Research Council of NZ funded the paired studies -the ‘Prospective Outcomes of Injury Study: 10 years on’ (POIS-10; HRC19/344) and ‘POIS-10 Māori: Outcomes and experiences in the decade following injury’ (HRC19/325) following cohorts of New Zealanders recruited between 2007 and 2009 following an injury ( Derrett et al, 2021 , Wyeth et al, 2021 ). These studies aim to understand longer-term health and well-being outcomes for cohorts of NZ adults, including specifically for Māori (NZ’s Indigenous population).…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative interviews with Māori POIS participants revealed that access to health services went beyond the issue of cost and included a lack of suitable times outside of work hours for treatment and rehabilitation appointments and issues with transport availability and/or difficulties in arranging childcare to attend these (Wyeth et al, in preparation). POIS-10 Māori [ 22 ] is investigating further reasons people have difficulty accessing healthcare for their injury.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, our findings are currently being used to inform the development of an intervention to help identify injured Māori who would benefit early on from greater care and support in order to optimise recovery and reduce the chance of adverse outcomes at 12-months post-injury. They will also inform future Māori EQ-5D-3L analyses and comparisons with 12-year post-injury outcomes for injured Māori as part of the POIS-10 Māori study [ 22 ] for which data collection has recently been completed (July 2021) and is now being prepared for analyses. Current and future findings will provide useful information for ACC and health providers as to how they can optimise care and improve outcomes for injured Māori.…”
Section: Discussionmentioning
confidence: 99%
“…While the Meihana Model was first proposed as a guide for clinical practice, 26 it has subsequently supported a wider range of health research. [27][28][29][30] Framing the research within the Meihana Model enabled explicit consideration of the model's component parts -Whakapapa (ancestral links), Hinengaro (mental health), Tinana (physical health), Iwi-Katoa (society-organisations), Taiao (environment), and Whānau (family). Central to this approach was the composition of the research team.…”
Section: Research Approachmentioning
confidence: 99%
“…This approach implements the early stages of the behavioural change framework presented by Michie et al, 25 with an exploration of the issue and context, and allows for the Meihana Model to guide analysis. While the Meihana Model was first proposed as a guide for clinical practice, 26 it has subsequently supported a wider range of health research 27-30 . Framing the research within the Meihana Model enabled explicit consideration of the model's component parts – Whakapapa (ancestral links), Hinengaro (mental health), Tinana (physical health), Iwi‐Katoa (society‐organisations), Taiao (environment), and Whānau (family).…”
Section: Parks and Reserves As Smokefree Environmentsmentioning
confidence: 99%